Incidência natural de parasitóides em ovos de percevejos (Hemiptera: Pentatomidae) encontrados na soja no distrito federal - Medeiros, Maria Alice de (1998)
A survey of egg parasitoids of soybean Pentatomidae was carried out in Planaltina, DF, Brazil. Twelve species of egg parasitoids (Telenomus edessae Fabricius, Telenomus podisi Ashmead, Telenomus sp., Trissolcus basalis (Wollaston), Trissolcus brochymenae Ashmead, Trissolcus sp., Trissolcus teretis Johnson, Trissolcus urichi Crawford; Anastatus auriceps Ashmead, Eupelmus sp., Ooencyrtus sp. and Neorileya sp.) were recovered in seven hosts: Acrosternum aseadum Rolston, Edessa meditabunda (Fabricius). Euschistus heros (Fabricius), Nezara viridula Linnaeus, Piezodorus guildinii (Westwood), Podisus nigrispinus (Dallas) and Thyanta perditor (Fabricius). For the first time new hosts were registered for A. auriceps (A. aseadum); T. teretis (E. heros and T. perditor) and T. urichi (A. aseadum, P. guildinii and P. nigrispinus).